2017
DOI: 10.1186/s12886-017-0454-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ocular biometric factors on the accuracy of various IOL power calculation formulas

Abstract: BackgroundTo evaluate how differences in ocular biometry affects the Hoffer Q, Holladay 1, SRK/T, and Haigis intraocular lens power calculation formulae predictions.MethodsThis study was performed on 91 eyes of 91 patients who underwent uneventful cataract surgery. Ocular biometry values were measured using the IOL Master 500, and intraocular lens (IOL) power was calculated using the Haigis, Hoffer Q, Holladay 1, and SRK/T formulas. We calculated the expected difference (ED) of each 3rd generation formula from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 18 publications
3
35
0
1
Order By: Relevance
“…This supports previously published research on biometric determinants for cataract and refractive surgery (Engren & Behndig ; Jeong et al. ; Plat et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…This supports previously published research on biometric determinants for cataract and refractive surgery (Engren & Behndig ; Jeong et al. ; Plat et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Jeong et al reported that preoperative ACD has the greatest influence in IOL power calculation of the third-generation formulas and the Haigis formula. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…4,5) Some studies have analyzed the influence of preoperative anterior chamber depth (ACD) on PPR in different IOL calculation formulas. 6,7) They concluded that the influence of preoperative of ACD on PPR varies from formula to formula. Other studies have examined the influence of pupil dilation on biometric parameters such as ACD, lens thickness (LT), white-to-white (WTW), and recommended IOL power using different IOL calculation formulas.…”
Section: Introductionmentioning
confidence: 99%